PRE-PLANTING LAND CULTIVATION IN UZBEKISTAN - Qobulov Makhammadjon Alijon ogli (Web of Journals Publishing, 2024)
This article discusses the fact that the most important and primary task in preparing the land for sowing seeds of cereals and other crops in Uzbekistan is the early spring harrowing of the fields and that if this agrotechnical measure is carried out promptly, the field surface will be soft and well-levelled, as a result of which the moisture accumulated in the soil will not rise and the emergence of weeds will be ensured.
Keywords: Cultivator, cereals, chisel, leveller, field, arrowhead, saline, passive, rotary, combined, operation, paw, seed, sow.